2017
DOI: 10.1097/ccm.0000000000002689
|View full text |Cite|
|
Sign up to set email alerts
|

Severe Burnout Is Common Among Critical Care Physician Assistants: Retracted

Abstract: Severe burnout is common in critical care medicine physician assistants. Higher patient-to-critical care medicine physician assistant ratios and provision of futile care are risk factors for severe burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Burn out was largely driven by emotional exhaustion with inciting factors including too many nonclinical duties and inadequate administrative and teaching time . Bhatt and colleagues evaluated rates of burn out in critical care physician assistants and found a similar rate of burn out (55.6%) that was directly related to patient volume …”
Section: Discussionmentioning
confidence: 99%
“…Burn out was largely driven by emotional exhaustion with inciting factors including too many nonclinical duties and inadequate administrative and teaching time . Bhatt and colleagues evaluated rates of burn out in critical care physician assistants and found a similar rate of burn out (55.6%) that was directly related to patient volume …”
Section: Discussionmentioning
confidence: 99%
“…(9) Unfortunately, there is a paucity of current ICU staffing data from LMICs and its relationship with outcomes. Previous information has demonstrated the association between both nurse staffing (26) and the intensivist-patient ratio (27) with hospital mortality and severe burnout, (28) but these data are mainly from high-income countries. In Brazil, Tironi et al observed a burnout prevalence of 61.7% in intensivists and the lack of resources as a stressor during ICU shifts in 47.4% of staff.…”
Section: Discussionmentioning
confidence: 99%
“…Survey questions were developed by the research team from the evidence of prior studies. 4,[11][12][13][14][15][16][17][18][19][20][21][22] The responses were graded on the Likert rating scale (strongly agree, agree, undecided, disagree, and strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
“…Intensive care professionals have the highest rate of BOS among all specialties, with 25% to 33% incidence of severe BOS among critical care nurses and up to 45% among critical care physicians. 4,[11][12][13][14][15][16][17][18][19][20][21][22] The critical care community has recognized that, in addition to providing care to patients and their families, it is essential to focus on emotional and psychosocial support for caregivers in the ICU. 4 "Closure" describes completion of a grieving process and may be achieved by attending funerals and services, sending condolence cards, or talking to bereaved families.…”
mentioning
confidence: 99%